Assessment of Sea Water Quality Around Sunken MV Ulla Ship on Iskenderun Bay, Hatay, Turkey - KEMAL SANGON, MUSTAFA; GOKSEL OZDILEK, HASAN (Asian Journal of Chemistry, 2010)
MV Ulla, which was a cargo marine vessel loaded with fly ash, ended its forced voyage at Iskenderun Port on February 20, 2000. The ship was abandoned there for 41/2 years. Finally, the vessel sunk on September 6, 2004. The load was removed from the vessel in order to comply with related regulations in summer 2005. This paper investigates the sea level metal levels between September 2004 and September 2005. It was found that total chromium during fly ash removal did not pass the upper limit of hazardous waste limits. Furthermore, total suspended solids decreased in recovery ship tanks as a function of time during the recovery process of load.